1999
DOI: 10.1111/j.1600-079x.1999.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melatonin treatment on 24‐hour rhythms of serum ACTH, growth hormone, prolactin, luteinizing hormone and insulin in rats injected with Freund's adjuvant

Abstract: The effect of melatonin injection on Freund's adjuvant-induced changes in levels and 24-hr rhythms of circulating ACTH, growth hormone (GH), prolactin (PRL), luteinizing hormone (LH), and insulin was assessed in rats. Animals received subcutaneous (s.c.) injections of melatonin (30 microg) or vehicle, 1 hr before lights off for 12 days. Ten days after melatonin treatment, they were injected with Freund's complete adjuvant or its vehicle s.c., and after 3 days, rats were killed at six different time intervals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This protective effect of SOD might be explained by correlating its activity pattern with the seasonal variation in internal melatonin level of F. pennanti [16]. The effects of melatonin on the levels of a number of biochemical variables, on hormones and on oxidative and antioxidative status in mammals, and how they change in relation to their circadian patterns, have been reported [47,48]. Besides being a circadian and seasonal biorhythm regulator, a wide spectrum of targets and effects of melatonin has evolved in a variety of tissues, such as the gut, cerebrospinal fluid, ovary, skin, bone marrow, bile fluid and lymphocytes, as well as in whole organisms [49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect of SOD might be explained by correlating its activity pattern with the seasonal variation in internal melatonin level of F. pennanti [16]. The effects of melatonin on the levels of a number of biochemical variables, on hormones and on oxidative and antioxidative status in mammals, and how they change in relation to their circadian patterns, have been reported [47,48]. Besides being a circadian and seasonal biorhythm regulator, a wide spectrum of targets and effects of melatonin has evolved in a variety of tissues, such as the gut, cerebrospinal fluid, ovary, skin, bone marrow, bile fluid and lymphocytes, as well as in whole organisms [49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivities of RIAs were 0.2, 0.04, 0.045, 0.097 and 0.048 ng/ml using the NIDDK rat ACTH-RP-1, rat GH-RP-2, rat prolactin RP-3, rat FSH-RP-2 and rat LH-RP-3, respectively. Results were expressed as pg/ml of plasma [25,[27][28][29] .…”
Section: Hormone Determinationmentioning
confidence: 99%
“…For this reason melatonin may affect -directly or indirectly -the metabolism of a given organism (Vanecek, 1998;Maćkowiak et al, 1999a, b). The advantageous effects of melatonin on carbohydrate-lipid metabolism (Maćkowiak et al, 1999a, b;Hoys et al, 2000) as well as on the endocrine status (Maćkowiak et al, 1999a;Esquifino et al, 1999;Fabiś et al, 2002) have already been demonstrated.…”
mentioning
confidence: 99%